2017
DOI: 10.1371/journal.pone.0184785
|View full text |Cite
|
Sign up to set email alerts
|

Optimal pseudorandom sequence selection for online c-VEP based BCI control applications

Abstract: BackgroundIn a c-VEP BCI setting, test subjects can have highly varying performances when different pseudorandom sequences are applied as stimulus, and ideally, multiple codes should be supported. On the other hand, repeating the experiment with many different pseudorandom sequences is a laborious process.AimsThis study aimed to suggest an efficient method for choosing the optimal stimulus sequence based on a fast test and simple measures to increase the performance and minimize the time consumption for resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Table 1 enumerates the studies that used these variations. In general, some studies suggested that the performance of BCIs based on time-delayed versions of a single bit-sequence does not vary significantly when using different code types [43][44][45].…”
Section: Bit-sequencesmentioning
confidence: 99%
“…Table 1 enumerates the studies that used these variations. In general, some studies suggested that the performance of BCIs based on time-delayed versions of a single bit-sequence does not vary significantly when using different code types [43][44][45].…”
Section: Bit-sequencesmentioning
confidence: 99%
“…Although to a lesser extent, Gold sequences have also previously been explored by Thielen et al [15] in another VEP-based paradigm consisting of asynchronously evoked broad-band VEPs, due to the optimal cross-correlation properties of such sequences. Similarly, while Kasami sequences have had a highly limited presence in BCI research, these demonstrated inconclusive results in the context of c-VEP modulation when studied in 2017 by Isaksen et al [28].…”
Section: Modulation Sequences (Mss)mentioning
confidence: 99%
“…First, the encoding method of c-VEP can be optimized. There are many kinds of pseudorandom codes with different characteristics (Kettunen 1997), and the code selection can influence the system performance (Isaksen et al 2017). In addition, the other stimulation parameters can also be considered, such as the monitor refresh rate, the stimulus pattern, the stimulus color, etc.…”
Section: Discussionmentioning
confidence: 99%